Effects of taper parameters on free spectral range of non-adiabatic tapered optical fibers for sensing applications - Musa, Baktiar; Mustapha Kamil, Yasmin; Abu Bakar, Muhammad Hafiz; Muhammad Noor, Ahmad Shukri; Ismail, Alyani; Mahdi, Mohd Adzir (Wiley Periodicals, 2016)
We investigated the effects of taper parameters on the free spectral range of transmission spectrum of non-adiabatic tapers. From experimental results, the optimum profile for the tapered fiber in terms of taper angle, waist diameter, and length are 11.500 mrad, 10 μm, and 20 mm, respectively.